CHARACTERISTICS OF BALI BEEF THIGH MEAT MARINATED WITH ROBUSTA COFFEE FILTRATE - H. J. B., Liemman; Oka, A.A.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
The purpose of this research was to knowed effection of robusta coffee filtrate on Bali beef thigh meat and to decide the concentration of the filtrate. The study using a completely CRD with four types of treatment, each repeated five times. The ftreatments were no marination (P0), 5% filtrate from robusta coffee (P1), 10% filtrate from robusta coffee (P2), and 15% filtrate from robusta coffee (P3). The variables which notice included the physical and organoleptic characteristics. The methods used were ANOVA for physical characteristics and non-parametric analysis for organoleptic characteristics. The results circumstances for physical characteristics, the pH from four treatments differed significantly (P<0.05) P0 with P1, P2, P3. Cooking loss differed significantly (P<0.05) with P0 to P1, as well as P0 with P1, P2, and P2 with P3. For organoleptic characteristics, color and tenderness showed differences of significant (P<0.05) with P0 and P1, P2, and P3. It was concluded that a 5% robusta coffee filtrate concentration (P1) provided the best results in influencing the characteristics of marinated Bali beef thigh meat.